A Versatile Plant Rhabdovirus-Based Vector for Gene Silencing, miRNA Expression and Depletion, and Antibody Production - Peng, Xingxing; Ma, Xiaonan; Lu, Shuting; Li, Zhenghe (Frontiers in Plant Science, 2021)
Plant virus vectors are ideal tools for delivery of genetic cargo into host cells for functional genomics studies and protein overexpression. Although a vast number of plant virus vectors have been developed for different purposes, the utility of a particular virus vector is generally limited. Here, we report a multipurpose plant rhabdovirus-based vector system suitable for a wide range of applications in Nicotiana benthamiana. We engineered sonchus yellow net rhabdovirus (SYNV)-based gene silencing vectors through expressing a sense, antisense, or double-stranded RNAs of target genes. Robust target gene silencing was also achieved with an SYNV vector expressing a designed artificial microRNA. In addition, ectopic expression of a short tandem target mimic RNA using the SYNV vector led to a signiﬁcant depletion of the target miR165/166 and caused abnormal leaf development. More importantly, SYNV was able to harbor two expression cassettes that permitted simultaneous RNA silencing and overexpression of large reporter gene. This dual capacity vector also enabled systemic expression of a whole-molecule monoclonal antibody consisting of light and heavy chains. These results highlight the utility of the SYNV vector system in gene function studies and agricultural biotechnology and provide a technical template for developing similar vectors of other economically important plant rhabdoviruses.